Validity of DCIP Method for Rapid Screening of Haemoglobin E Trait - Ahmed, Abul Kashem Jalaluddin; Khondaker, Tarannum; Amin, Syed Khairul (Anwer Khan Modern Medical College Journal, 2020)
Background: Hemoglobin E B thalassemia is the commonest thalassemia syndrome in Bangladesh. All tests for diagnosis of Hb E trait are expensive,time consuming and require sophisticated equipment. The need therefore, is a simple,low cost ,rapid and reliable test which can be used for mass screening of E trait. The present study was designed to see the validity of DCIP test as screening test for detection of E Trait. Methodology: A cross sectional observational study was conducted at Dhaka Shishu (Children) Hospital from December 2008 to November 2009. Total 150 subjects attending Dhaka Shishu Hospital Thalassemia centre were selected and evaluated for Hb estimation, RBC indices, Hb Electrophoresis and DCIP test. According to electrophoresis results patients were divided into 3 groups. Group I comprised of 50 subjects with Hb E trait, group II comprised 51 subjects with ß thalassemia trait and Group III comprised of 49 normal subjects. In all 3 groups DCIP test was done and in positive cases, precipitated haemoglobin was visualized by naked eye at the bottom of the test tube. Negative samples with normal electrophoresis and ß thalassemia trait were used to see the samples gave false positive result. Results: The test successfully detected 48 subjects among total 50 subjects of E trait. DCIP sensitivity, specificity, positive predictive value and negative predictive values were 96%,97%,94.12% and 97.97% respectively. Conclusion: DCIP has high sensitivity, specificity, positive and negative predictive value. So, it might be considered as a valid single screening test to detect E Trait in areas with limited laboratory facilities and economic resources. AKMMC J 2020; 11(2) : 113-119